2019
DOI: 10.1159/000505241
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antiplatelet Therapy after Intravenous Thrombolysis for Acute Minor Ischemic Stroke

Abstract: Objective: To verify the efficacy and safety of dual antiplatelet therapy after intravenous thrombolysis for acute minor ischemic stroke (AMIS). Methods: AMIS patients who received recombinant tissue plasminogen activator (rt-PA) intravenous thrombolysis from January to October 2018 were retrospectively analyzed and divided into the aspirin (ASP) and ASP + clopidogrel (ASP-CLO) groups based on the type of antiplatelet therapy to compare the rates of good clinical outcome, symptomatic intracranial hemorrhage (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The 0.9% rate of sICH with alteplase in this study was comparable to other studies of Chinese patients with minor stroke who were treated with alteplase (0%-1.0%). 18,19 The strengths of this randomized trial were its large sample size, multicenter recruitment, and dual antiplatelet strategy, which enhances the generalizability of the results. Age, sex, medical history, time from onset of symptoms to treatment, and presumed stroke cause in the trial were similar to routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The 0.9% rate of sICH with alteplase in this study was comparable to other studies of Chinese patients with minor stroke who were treated with alteplase (0%-1.0%). 18,19 The strengths of this randomized trial were its large sample size, multicenter recruitment, and dual antiplatelet strategy, which enhances the generalizability of the results. Age, sex, medical history, time from onset of symptoms to treatment, and presumed stroke cause in the trial were similar to routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many neurologists tend to conservatively use single antiplatelet therapy (aspirin or clopidogrel) for patients with minor stroke who received thrombolysis (31). We noticed an article published by Dr. Zhang (23) in which the authors verified the efficacy and safety of dual antiplatelet therapy after IVT to some extent. They enrolled patients with acute minor ischemic stroke with a NIHSS score ≤ 5.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, both rt-PA thrombolytic therapy and antiplatelet treatment have potential bleeding risks and other complications (19)(20)(21)(22), which are worrying in real-world practice, leading to different strategies of antiplatelet treatment for patients with minor stroke receiving IVT. A previous study reported the safety and efficiency of 21-day dual antiplatelet therapy in patients who received IVT compared with single antiplatelet therapy (23). However, no guidelines or large randomized clinical trials have yet identified an antiplatelet strategy under this scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Antiplatelet agents can be recommended as a secondary prevention measure in ischemic stroke (Arnold et al, 2016;Majid et al, 2001;Zhao et al, 2019). However, the use of antiplatelet agents for secondary prevention of ischemic stroke in patient with CKD has not been robustly supported by evidence till date (Kelly & Rothwell, 2019).…”
Section: Antiplatelet Agentsmentioning
confidence: 99%